Yeasts charakteristics and identification - Barnett, J. A; Payne, R. W; Yarrpw, D (Cambridge University Press, 2000)
This new edition of the most comprehensive yeast identification and reference manual ever published has been completely revised and expanded to include almost 100 additional species and nearly 500 additional photomicrographs. Over half of the volume describes the 678 currently recognized species in a clear, easy to use layout with over 1300 high-quality photomicrographs. Readily usable keys and tables allow identification of all of the species described and a wealth of reference information broadens the scope of the book beyond identification.
Keywords: biochemie